The Performance of the Health Care System in Yemen before and after the War - Ahlam Esmail Alnaqeb (Recent Progress in Science and Technology Vol. 8, 2023)
This paper seeks to assess the performance of the healthcare system in Yemen pre- and during-conflict 2010-2020 and to examine the impact of the conflict on the healthcare system performance during the period 2015-2020. Yemen’s prolonged war has ravaged its energy system. Fighting, underfunding, and diesel shortages have wreaked havoc on the nation’s underdeveloped power grid and left communities and cities without electricity Yemen is facing one of the worst humanitarian crises in the world due to the ongoing conflict that has begun in 2013. A literature review from 2010 to 2020 of the evidence reported by international and local organizations as well as in published and unpublished articles and reports. The study used the Building Blocks framework developed by the WHO (2007; 2009) (hereafter WHO-BB). According to the findings before the war, Yemen’s healthcare system was plagued by governance issues and corruption, a significant funding gap in the healthcare sector, an uneven distribution of healthcare workers, lax pharmaceutical regulations, and inadequate health information. Additionally, the effects of war on the healthcare system were catastrophic. Yemen’s healthcare system is ineffective and disjointed. The government needs to restructure the domestic healthcare industry with the assistance of global health organisations in order to resolve this problem.